The Effect of Remuneration and Job Satisfaction on Employee Performance in Public Works and Spatial Planning Agency (PUPR) of Seluma Regency - Yen Vesno; Ahmad Soleh; Sri Handayani (Penerbit Jurnal Indonesia, 2021)
The aim of this study is to determine the effect of remuneration and job satisfaction on employee performance at Public Works and Spatial Planning Agency (PUPR) of Seluma Regency.The sample in this study were all employees at the Public Works and Spatial Planning Agency (PUPR) of Seluma Regency who had become State Civil Servants (ASN) as many as 52 people. The sampling method is by means of a census. The data collectiontechnique by means of a questionnaire. The analytical method used is multiple regression analysis, hypothesis testing t and hypothesis testing f.The regression equation results are Y = 6.045 + 0.419X1 + 0.458 X2 with a positive regression direction, meaning that if there is an increase in remuneration and job satisfaction, the performance will also increase. Remuneration has a significant effect on employee performance at Public Works and Spatial Planning Agency (PUPR) of Seluma Regency. This is evidenced by the results of partial hypothesis testing (t test) that the significant value of 0.000 is smaller than 0.05. This means that if the remuneration increases, the employee performance will also increase. Job satisfaction has a significant effect on employee performance at Public Works and Spatial Planning Agency (PUPR) of Seluma Regency. This is evidenced by the results of partial hypothesis testing (t test) that the significant value of 0.000 is smaller than 0.05. This means that if organizational commitment increases, employee performance will also increase. Remuneration and job satisfaction have a significant effect together on the employees performance at Public Works and Spatial Planning Agency (PUPR) of Seluma Regency. This is evidenced by the results of simultaneous hypothesis testing (f test) that the significant value is 0.000 less than 0.05.